Coping with COVID-19 Impact on Self-Employment: Does Gender and Academic Education Matters? - THAPA, Manish (Journal of Research in Educational Sciences; Vol 11 No 1 (2020): JRES Volume XI Issue 1(13), 2020DO - 10.14505//jres.v11.13.03, 2020)
In this modern age of competitiveness and the quest for sustainable income source through adoption of innovative approaches, the preference towards self-employment is ever increasing among individuals in global scenario. In Nepali scenario, as the rate of employment opportunities are comparatively low in comparison to rate of individual obtaining higher degree (above high school), rate of self-employed individuals has increased in significant manner. As financial security is not as strong as that of developed countries, self-employment sector gets affected during any unwanted circumstances which were evident during COVID-19 period as well. This paper used Human Capital Theory and Need for Achievement Theory to discuss role of gender and academic knowledge as contributing factors towards identification and adoption of coping strategies during COVID-19. With desk review and interviews with self-employed individuals, this paper strongly argues, the strategies adopted to cope with COVID-19 is more guided by enterprise type and financial backing instead of academic skill and gender.